New insights on how rainfall patterns influence arsenic in rice - Sadaf, Bushra Humaira; Habib, Muhammad Ashraful (International Rice Research Institute, 2025)
Arsenic in rice has long been linked to contaminated irrigation water, especially in the dry-season Boro crop. But new research in Bangladesh which covers 943 sites shows that rainfed systems also play a role, and understanding this better can help shape safer, more sustainable rice production. The study recently done by IRRI and Cranfield University looked at three rice seasons: Boro (irrigated), Aus (rainfed, short-duration during the monsoon), and Aman (rainfed, longer-duration into the dry season). Results showed that arsenic permitted threshold in rice grain were lowest in Aman, higher in Boro, and highest in Aus. Importantly, Aman rice was very safe, with only 2% of samples above international food safety limits. Boro and Aus rice had higher percentages, at 25% and 41% respectively.